Access to Czech Administrative Courts – Bottlenecks in Access to Justice - Skládalová, Denisa; Hrubešová, Sára; Svoboda, Tomáš (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The right of access to a court is subject to certain limitations. While a number of these limitations may be created deliberately, in line with the function of the administrative justice system (e.g. restrictions on review by the higher courts, others may be more or less unintended consequences of the design of the administrative justice system (or application of relevant rules or case law). The article attempts to present possible forms of these limitations and tries to outline some of the main “bottlenecks” in the access to judicial protection in the context of Czech administrative justice. These limitations can be regarded mainly as formal and informal, and their recognition can result in increasing the efficiency of the functioning of judicial protection, in particular by simplifying procedural regulation in relation to the ongoing societal and technical changes.